The Difference between Human and Animal in the Perception of Children in Early School Age - Nowicki, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2022)
The article describes how children perceive the difference between humans and animals. Classic definitions of species difference known from philosophy or theology differ significantly from the meanings that children describe to differences between the human and animal worlds. At the same time, in many theories of education, the child and childhood are perceived as belonging to the world of nature. Therefore, the question about children's ways of perceiving the species difference seems to be particularly important from the perspective of education and cultural anthropology. Based on interviews with children, the text shows the meanings and consequences of placing the meanings of the species difference in the ways of obtaining and consuming food. Interpreting the collected empirical material with the help of critical discourse analysis, we can see the polysemic nature of the species difference understood in this way, the functions of which are generated by cultural, religious and species divisions.